A Multi‐Hazard Risk Framework to Stress‐Test Water Supply Systems to Climate‐Related Disruptions. Issue 1 (4th January 2023) - Becher, Olivia; Pant, Raghav; Verschuur, Jasper; Mandal, Arpita; Paltan, Homero; Lawless, Mark; Raven, Emma; Hall, Jim
Abstract: Water utilities' supply systems are vulnerable to several climate‐related hazards, including droughts, floods and cyclones. Here we propose a generally applicable framework for conducting multi‐hazard risk assessments of water supply systems and use it to quantify the impact of present and future climate extremes on the national water supply network in Jamaica. The proposed framework involves stress‐testing a model of the system with a large set of spatially coherent drought, cyclone and pluvial and fluvial flood events to calculate the number of water users whose supplies would be disrupted during an event, that is, the Customer disruption days (CDD). We estimate the total multi‐hazard annual expected disruption to be approximately 5 days per year per utility customer under present conditions. This is increased by a factor of between 2 and 2.5 when end‐of‐century climate scenarios are propagated through the model. Our analysis shows that more high probability drought events lead to greater CDD compared with asset damage events. However, extreme asset damage events, despite manifesting over shorter timescales (days) compared to drought events (months), can lead to more widespread CDD. This quantified risk framework would allow utility managers to compare the risk of both asset damage‐ and water shortage‐induced disruptions via a common, decision‐relevant metric. However, applications to other utilities would require tailored hazard modeling approaches. The proposed risk assessment is intended to inform prioritization of infrastructure investments, ranging from asset protection to drought mitigation projects, with the goal of enhancing water supply resilience in the face of a changing climate. Key Points: We propose a spatial multi‐hazard risk framework for analyzing present‐day and future climate risks to water users We propose the use of customer disruption days as a common metric for comparing different hazards impacts The framework can be used by decision makers to prioritize investments across asset protection against flooding and cyclones, and drought mitigation options